Critical Rationalism as a Source of Theoretical Jurisprudence - R. S. Raab (Теоретическая и прикладная юриспруденция)
The article is devoted to the inquiry of a speciﬁc conception of law, emerging from an attempt to comprehend sociolegal order through the lens of epistemology of critical rationalism. Taking as an example the works of Friedrich Hayek, one of the leading theorists who applied critical-rationalist epistemology to the study of society, we describe the key tenets of this epistemology, as well as its implications for social science. According to our hypothesis, the key tenets of critical-rationalist epistemology can produce not only a certain social philosophy, but also a certain view on the main questions of legal theory. The questions of the function of law, its structure and evolution, being studied by its theoretical reconstruction in the context of the critical-rationalist epistemology, indicate the signiﬁcant relevance of the epistemology of critical rationalism as the basis of a coherent legal theory. The legal theory, which consider law as an endogenously evolving “compositive” (dispersed) social structure, preventing epistemically unjustiﬁed intervention of organized power actors into spontaneous social order. This perception of law, based on the epistemology of critical rationalism, opposes the currently dominant “Cartesian-rationalist” theory of law as an exogenously designed by political legislator logical normative structure, serving as a technical tool of epistemically unjustiﬁed intervention of organized power actors into spontaneous social order. And though this Cartesianrationalist legal theory is the opposite of the critical-rationalist concept of law, the very identiﬁcation of these two types of legal theory is becoming possible only when we analyze law through the lens of the epistemology of critical rationalism.